African futures - Greiner, Clemens; Wolputte, Steven van; Bollig, Michael (African-Europe Group for Interdisciplinary Studies, 2022)
"The essays in this collection are written to make readers (re)consider what is possible in Africa. The essays shake the tree of received wisdom and received categories, and hone in on the complexities of life under ecological and economic constraints. Yet, throughout this volume, people do not emerge as victims, but rather as inventors, engineers, scientists, planners, writers, artists, and activists, or as children, mothers, fathers, friends, or lovers - all as future-makers. It is precisely through agents such as these that Africa is futuring: rethinking, living, confronting, imagining, and relating in the light of its many emerging tomorrows"--